4 Answers: A, C, E, and F
================================================
Step-by-step explanation:
Choice A is true assuming we have
![a_n = (-1)^n*b_n](https://img.qammunity.org/2021/formulas/mathematics/college/3wu53wj12zr0b3u9cqcut1lr9n3qc5xpkb.png)
In this case,
and
![b_n = (1)/(√(n))](https://img.qammunity.org/2021/formulas/mathematics/college/lh5du04bbqffz2umo6piaph2ghowtveyqs.png)
--------
Choice B is false. See choice A above.
--------
Choice C is true. The sequence
is decreasing. As n gets larger,
gets smaller. This is because the denominator is growing larger with the numerator held constant.
--------
Choice D is false. This contradicts choice C.
--------
Choice E is true since the denominator is growing forever
This is similar to
![\displaystyle \lim_(n \to \infty) (1)/(n) = 0](https://img.qammunity.org/2021/formulas/mathematics/college/ohtqhupejtoapjea1v8j2lx5ewz9inl4dc.png)
--------
Choice F is true due to choices C and E being true.
--------
Choice G is false because it contradicts choice F.